Pengaruh Emotional Intelligence, Organizational Commitment, dan Job Satisfaction terhadap Organizational Citizenship Behavior pada PegawaiInstansi Pemerintah: Studi pada Kantor Vertikal Ditjen PerbendaharaanProvinsi Sulawesi Barat - Husni; M Said Abdullah; Rezki Wardani (Pascasarjana Universitas Muhammadiyah Mamuju, 2026)
This study aims to analyze the effects of emotional intelligence, organizational commitment, and job satisfaction on organizational citizenship behavior (OCB) among employees of the Vertical Offices of the Directorate General of Treasury in West Sulawesi Province. This study employed a quantitative approach using a survey research design. The research sample consisted of 67 respondents selected through the total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, multiple linear regression analysis, partial significance tests (t-test), simultaneous significance test (F-test), and the coefficient of determination (R²). The results indicate that emotional intelligence, organizational commitment, and job satisfaction each have a positive and significant effect on organizational citizenship behavior. Simultaneously, the three independent variables also have a significant positive effect on OCB. The novelty of this study lies in simultaneously examining these three variables in the context of government employees in West Sulawesi, a public-sector setting that remains relatively underexplored. These findings imply that strengthening employees’ emotional intelligence, organizational commitment, and job satisfaction can serve as an effective strategy for promoting positive employee behavior within public sector organizations